Edukasi Diet Anti inflamasi Berbasis Pangan Lokal Bulukumba sebagai Upaya Mengurangi Nyeri Menstruasi pada Mahasiswa Akademi Kebidanan Tahirah Al Baeti Bulukumba - Nadiatul Khaera (Lembaga Pengembangan Kinerja Dosen, 2026)
Menstrual pain (dysmenorrhea) is a common complaint among female students and can affect concentration, academic activities, and quality of life. One non-pharmacological effort that can be done to help reduce this complaint is through the implementation of an anti-inflammatory diet based on local foods. This community service activity aims to increase students' knowledge about the concept of an anti-inflammatory diet and the use of local foods in Bulukumba as an effort to prevent and reduce menstrual pain. The activity was held on Wednesday, June 17, 2026, in the Hall of the Tahirah Al Baeti Bulukumba Midwifery Academy, involving 18 students. The implementation method included counseling, interactive discussions, questions and answers, demonstrations of local food-based menu examples, and distribution of educational leaflets. The final evaluation was carried out through questions and answers and simple questions to measure the level of participant understanding after the activity. The evaluation results showed an increase in students' knowledge about the anti-inflammatory diet. Of the 18 participants, 13 students (72.2%) had a good level of knowledge, while 5 students (27.8%) had a fair level of knowledge regarding the concept of an anti-inflammatory diet, its benefits in reducing menstrual pain, and the use of local Bulukumba foods as anti-inflammatory food sources. This activity demonstrated that local food-based health education can improve students' knowledge as a promotive and preventive measure in managing dysmenorrhea.